Development and evaluation of a battery operated ginger (Zingiber officinale) washer for small and marginal farmers - KUMAR, T V ARUN; ARADWAD, PRAMOD P; JAISWAL, PRANITA; RATHOD, SANTOSHA; SAHOO, P K; MANI, INDRA (The Indian Journal of Agricultural Sciences, 2022)
Ginger (Zingiber officinale Rosc.) is a commercial crop grown for its aromatic rhizomes which is used both as a spice and medicine. Being a root crop and owing to its physical structure, ginger rhizomes contain heavy soil load which makes washing as an important and prime post-harvest operation. Manual washing of ginger is a laborious and time consuming process. An experiment was conducted at the ICAR-Indian Agricultural Research Institute, New Delhi during 2020 with an objective to develop a continuous rotary drum type battery operated ginger washer and to evaluate its performance.The machine consists of the frame, feeding and discharge chutes, rotary drum with internal flights, pressure pump and nozzle assembly, battery and a drive unit. The developed washer was evaluated at different feed rate and residence time to appraise the washing efficiency, microbial washing efficiency, bruise index and colour of washed ginger. Increase in feed rate significantly reduced the washing and microbial efficiencies but increased mechanical damage. Washing and microbial efficiencies increased with increase in residence time.Significant difference in the colour was found between washed and unwashed ginger.The best set of conditions under which the washer could be operated was 150 kg/h and 25 sec, at which the machine was found to have mechanical washing efficiency of 92.48%, microbial washing efficiency of 93.18% and 4.54% bruise index. Besides eliminating drudgery of washing operation, the developed washer was found to save time, water and operating cost as compared to manual washing.